What Are You Going to Do with That Major?: The Humanities, Jobs, and a Career - Counihan, Patricia (Maine Policy Review, 2015)
Based on years of experience in a university career center, Patricia Counihan outlines the value to both employers and future employees of the curiosity, flexibility, and open-mindedness that humanities majors develop through their coursework. A humanities education allows students to thrive in many careers and to be flexible, creative employees.
Keywords: humanities; college majors; employment; University of Maine